PENERAPAN COGNITIVE BEHAVIOR THERAPY (CBT) UNTUK MENINGKATKAN SELF-REGULATION PADA PENGGUNA AMPHETAMINE DI BALAI BESAR REHABILITASI BADAN NARKOTIKA NASIONAL LIDO SUKABUMI - Azka, Azka (SENATIK STT Adisutjipto, 2017)
Self-regulation on drug users is the key that they are able to get away from the addiction especially after discharge from rehabilitation. Drugs addict needs self regulation in effort to get away from drugs addiction. In order toimprove self-regulation, researcher had been applying cognitive behavior therapy (CBT). the method used in the study is basic single-case experimental with A-B-A design. The Result of this study is cognitive behavior therapy can improve self-regulation on amphetamine users.